The Potential of Hydroponic Kit-Based Growing on a Self-Fertigation System for Pagoda Mustard (Brassica narinosa L) Production - Sophia Dwiratna; Kharistya Amaru; Muhammad Achirul Nanda (The Scientific World Journal)
Agricultural land has been converted into settlements following the population growth in various parts of the country. The productivity of horticulture, particularly pagoda mustard (Brassica narinosa L), decreases with the narrowing of fields. The main milestone as a promising solution to overcoming this issue is applying the hydroponic technique. This study aims to analyze the potential of hydroponic kit-based growing on a self-fertigation system for pagoda mustard production. In contrast to general hydroponic, the proposed hydroponic kit is supported by a smart valve component as a unique novelty used for the automatic distribution of nutrients without electrical power (zero energy). The mustard seeds were sown on rockwool for two to three days in a dark room and placed in the sun for seventeen days. A total of 50 pagoda mustard seeds were arranged evenly on a self-fertigation system tray following a zig-zag planting pattern for forty days. The seed has the following morphological characteristics: average height of 22.88 cm, biomass width of 26.42 cm, root length of 23.4 cm, and weight of 241.5 g. Furthermore, the production requires a total fertigation consumption of 186 L (equal to 0.0935 L/plant day−1) with an actual crop coefficient between 0.01 and 0.54. The proposed system shows good performance for mustard growth with a uniformity value between 80 and 89%. Finally, hydroponic kit-based growing on a self-fertigation system can be applied in various areas to produce and maintain a sustainable food supply.